Self-interaction-correction and electron removal energies - Reinhard, Paul-Gerhard; Suraud, E. (Theoretical Chemistry Accounts, 2021)
The paper addresses the problem of the self-interaction correction (SIC) in static calculations of atoms and molecules. Key observable is the electron removal energy, the energy required to remove one electron from the given system and to leave it in a definite hole state whereby we discuss hole states not only in the Highest Occupied Molecular Orbital (HOMO), but also deeper lying holes. To that end, we employ a newly developed technique to compute a stationary state for a configuration with a definite hole in a chosen single-particle state. We also compare two different definitions of removal energies, first, the genuine one taking the difference of the total energy of the original system and the energy of final system sustaining the hole, and second, simply the single-particle energy in the original system. According to Koopman's theorem, both should be close to each other. Four different systems are considered, one atom and three molecules with different bond types, covalent, metallic, and dipolar. The general result is that any SIC brings considerable improvement as compared to the initial Local-Density Approximation (LDA), the better the closer the hole stays to the HOMO. There are variations between different SIC approximations whereby systems with strong binding (atom and covalent molecule) show least variations. Here, the quality of Koopman's theorem is very satisfying for the HOMO and degrades slightly toward deeper binding. Systems with metallic or dipolar binding are more reactive and show stronger changes with approximation and hole level.
CRIS-Team WoS Importer:2021-05-28